2020
DOI: 10.18488/journal.62.2020.73.131.145
|View full text |Cite
|
Sign up to set email alerts
|

Does Capital Structure Affect the Profitability of Listed Family and Non-Family Firms? Evidence from Bangladesh

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…La porta et al (1999) identify family-dominated firms at 20% cut-off point, which is later followed in the studies of Cascino et al (2010) and Setia-atmaja et al (2011). Following the argument of Cascino et al (2010) not to rely on a single measure of identifying family firms, this study considers the characteristics suggested by Meah (2021) to segregate family firms from non-family firms. Meah (2021) identifies family firms: (a) using the non-financial data of annual reports, where the relationship between chairman and CEO/MD is clearly stated—if the chairman and CEO/MD of a firm are from the same family that firm is defined as family-controlled firms; (b) using the position of female director as chairman or CEO/MD—if a firm is run by a female head that firm is identified as family firm but this condition is kept out of consideration in case of MNCs; (c) using the surname of board of directors—if the corporate board of a firm consists of more than 50% directors including chairman and CEO/MD with the same surname that firm is referred to family-led firm; and (d) using the primary data—if there is a doubt on the identification of firm types, information from reliable person related to that firm is used to define whether the firm is running with family-dominance.…”
Section: Methodsmentioning
confidence: 99%
“…La porta et al (1999) identify family-dominated firms at 20% cut-off point, which is later followed in the studies of Cascino et al (2010) and Setia-atmaja et al (2011). Following the argument of Cascino et al (2010) not to rely on a single measure of identifying family firms, this study considers the characteristics suggested by Meah (2021) to segregate family firms from non-family firms. Meah (2021) identifies family firms: (a) using the non-financial data of annual reports, where the relationship between chairman and CEO/MD is clearly stated—if the chairman and CEO/MD of a firm are from the same family that firm is defined as family-controlled firms; (b) using the position of female director as chairman or CEO/MD—if a firm is run by a female head that firm is identified as family firm but this condition is kept out of consideration in case of MNCs; (c) using the surname of board of directors—if the corporate board of a firm consists of more than 50% directors including chairman and CEO/MD with the same surname that firm is referred to family-led firm; and (d) using the primary data—if there is a doubt on the identification of firm types, information from reliable person related to that firm is used to define whether the firm is running with family-dominance.…”
Section: Methodsmentioning
confidence: 99%
“…The sample in the study are all firms listed at the Nairobi Securities Exchange from 2008 to 2013. As reported by Meah, Chaudhory and Khalil (2020), they had examined the relationship between capital structure and firm performance in Bangladesh. The sample used are 39 non-family firms and 39 family firms.…”
Section: Empirical Evidencementioning
confidence: 99%
“…There are several options usable for companies assess its financing such as preferred equity, common shares, long-term debt, short-term debt and retained earnings. Besides, companies can choose to utilize a small amount of debt financing or a large portion of debt financing as their own strategies and options (Meah, Chaudhory, and Khalil, 2020). A company would have secured debt rather than risky debt when it is impossible to avoid levered and company will issue the common stock as equity financing for a last step (Abor, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The findings reveal that effective management of CS positively relates to firms' profitability measured in terms of ROA. Meah et al (2020) also examined the FP of 39 family firms and 39 non-family firms registered at Dhaka Stock Exchange with reference to CS and collected data during 2013-2017. The finding extracted using pooled OLS technique reveals that family firms are substantially influenced by debt financing as compared to non-family firms which favors pecking order theory.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…This section covers the results of multiple regression analysis and we have applied pooled OLS technique and fixed effect model in accordance with extant literature (Meah et al, 2020;Miko & Para, 2019;Mujwahuzi & Mbogo, 2020). The findings initially represent the FP of all the sectors (overall) with reference to CS.…”
Section: Findings-multiple Regression Analysismentioning
confidence: 99%